Performance optimization of physical layer security in STAR-RIS aided NOMA system - LI Meiling; WANG Yumin; WANG Sijing; ZHANG Haijun (Tongxin xuebao)
The strong coupling characteristics of the imperfect channel state information and the imperfect successive interference cancellation makes it faces the great challenge in evaluating the secure performance accurately for the simultaneously transmitting and reflecting reconfigurable intelligent surface (STAR-RIS) aided non-orthogonal multiple access (NOMA) transmission systems. To address this issue, a mixed algorithm based on penalty dual decomposition (PDD) and block coordinate descent (BCD) was proposed for optimizing the beamforming vectors at the base station and the phase-shift coefficients of the STAR-RIS jointly, aiming to maximize the minimum secure transmission rate of the system. The results demonstrate that minimum secure transmission rate can be significantly enhanced by the proposed mixed algorithm compared to that by BCD algorithm, achieving the performance improvement by at least 10%.